Anatomical study of the guinea pig glans (Cavia porcellus) of the Peru breed - Márquez F., Nattaly (2019)
The purpose of the study was to describe the macroscopic and microscopic characteristics of the structures that conforms the penis glans of the Peruvian guinea pig, and changes in the structure related to animal age. The study was conducted in 24 guinea pigs distributed in four age groups (1, 2 3, 5 months) of the Peru breed, where 20 samples taken for the macroscopic study and four for the microscopic study. The glans external surface is covered by small corneous scales of convex edge with tiny spicules directed to cranial. In the dorsal and ventral-lateral surfaces is observed the presence of extended and well-developed scales that are convex and have a free edge, with spicules directed dorsal-cranial. The glans sac is located dorsal to the penile urethra and the internal wall is covered by small scales and longitudinal folds and contains a pair of keratinaceous styluses. The os penis has an extended shape and related to the ventral surface of the glans. The glans showed a transition epithelium and lax vascular tissue. The stylus processes have a thick corneous layer of keratin and the os penis is formed of spongy bone tissue. The free end of the stylus processes becomes sharper, divergent and in some cases asymmetric with age.